Gain-scheduling control of vapor compression cycle for transient heat-flux removal. (June 2015) - Yang, Zehao; Pollock, Daniel T.; Wen, John T.
Abstract: Two-phase cooling is attractive for high heat-flux applications arising in high-power electronics such as LEDs, all-electric vehicles, and radar systems. A key challenge is critical heat-flux that could cause device damage due to dryout. This paper discusses a systematic design of robust and gain-scheduled controls for dryout avoidance in vapor compression cycles. Linear models from various operating points (OP) are clustered to reduce model nonlinearity. H ∞ controllers are synthesized to reach local robust stability. The gain-scheduled controller combining local controllers and OP switching shows excellent disturbance rejection performance in experimental comparison with the open-loop operation. Abstract : Highlights: The key objective of control for transient/electronics cooling is dryout avoidance. Nonlinearity is better divided with endogenous signals than evaporator heat-load. A gain-scheduled controller was designed by blending local robust controllers. Static optimization guarantees optimal and safe operations of VCC at steady state. Combining control and operating point switching enhances disturbance rejection.